2023
DOI: 10.1088/1748-605x/acc99a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of different biodegradable membranes in guided bone/tissue regeneration: a systematic review and network meta-analysis

Abstract: Guided bone/tissue regeneration (GBR/GTR) is commonly used in dental treatment. The desired bone/tissue regeneration is achieved by placing a barrier membrane over the defect to avoid the downward growth of faster-growing connective and epithelial tissue into the defect. This review aimed to evaluate osteogenic properties, degradation characteristics, and postoperative complications of eight biodegradable membranes in animal experiments, including non-crosslinked collagen membrane (NCCM), crosslinked collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 137 publications
(265 reference statements)
0
1
0
Order By: Relevance
“…Owing to their unique characteristic of directly forming a solid membrane or matrix within the defect, cross‐linkable hydrogels have been introduced to streamline the clinical handling of GBR 5 . Studies have reported that self‐setting polyethylene glycol is as efficacious as a collagen membrane in treating bony dehiscence defects surrounding dental implants 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unique characteristic of directly forming a solid membrane or matrix within the defect, cross‐linkable hydrogels have been introduced to streamline the clinical handling of GBR 5 . Studies have reported that self‐setting polyethylene glycol is as efficacious as a collagen membrane in treating bony dehiscence defects surrounding dental implants 6 .…”
Section: Introductionmentioning
confidence: 99%